Radicular Cysts and Periapical Granulomas: Data Documentation for 696 Cases and Findings on Fibrosis, and Porphyromonas gingivalis and Fusobacterium nucleatum in These Lesions - Sirke Virkkunen; Terhi Kaarela; Merja Laine; Auli Suominen; Jaana Hagström; Timo Sorsa; Caj Haglund (Clinical and Experimental Dental Research)
ABSTRACT Objective The objective of our study was to re‐evaluate periapical lesions, including radicular cysts (RCs) and periapical granulomas (PGs) for locations, histopathological features, and degree of fibrosis in relation to the inflammatory response. In addition, we examined the presence of Porphyromonas gingivalis (Pg) and Fusobacterium nucleatum (Fn) since both are widely recognized pathogens in periodontal infections. Methods We re‐evaluated samples of RCs and PGs (n = 728) and collected data for analyses by IBM's SPSS Statistics. Among these samples, we stained 93 samples to determine the immunoexpression of Pg and Fn. For immunostaining, we used Gingipain R1 antibody for Pg and Rabbit anti‐Fn antibody for Fn. Results Fibrosis is associated with mild inflammation. We found a significant positive correlation between Pg and Fn. Thus, these pathogens are likely to occur together in periapical inflammatory lesions. We additionally noted that these periodontopathic pathogens are more likely to be present in RCs than in PGs. Conclusions Asymptomatic radiologically diagnosed periapical lesions may not necessarily need root canal retreatment in healthy patients since these lesions may represent scar tissue rather than active apical periodontitis. Clinical and radiological follow‐up is still needed. Yet, periapical lesions, especially cysts, may contain dystopic periodontopathic pathogens, and Pg and Fn often occur together in periapical lesions.